Northern Bobwhite habitat selection during the nonbreeding season in a riparian corridor in Colorado - Joseph M Wolske; Adam C Behney; Larkin A Powell (Avian Conservation and Ecology, 2025)
Northern Bobwhites ( Colinus virginianus ) are a popular game species but also considered a species of conservation concern due to range-wide population declines. Colorado lies at the far northwest corner of the bobwhite range, where individuals generally face more extreme winter conditions than areas further south and east, where most bobwhite research has taken place. These edge-of-range climatic extremes may lead to differences in the utility and selection of various vegetation types and structures than those reported in studies from other regions in the bobwhite range. We used radio-marked bobwhites to assess habitat selection and movements during two nonbreeding seasons in a riparian corridor in northeastern Colorado. Bobwhites selected for greater visual obstruction (β vis = 0.026, SE = 0.005, P < 0.001), percent litter cover (β litter = 0.017, SE = 0.006, P = 0.004), and percent bare ground (β bare = 0.013, SE = 0.007, P = 0.045). Mean daily movement distance was 247.3 m (SE = 10.4), and mean nonbreeding home range size was 50.3 ha (SE = 4.8). Surprisingly, we did not find selection for woody vegetation, which is commonly reported in other studies. Otherwise, our results were consistent with research from other regions, and confirm the importance of maintaining areas with high visual obstruction interspersed with bare patches.